Pengembangan E-Modul Berbasis Experiential Learning - Storytelling untuk Penguatan Sosial-Emosional Mahasiswa PPG - Tuti Mutia; Sumarmi Sumarmi; Ardyanto Tanjung; Yusuf Suharto; Ravinesh Rohit Prasad; Donna Boedi Maritasari; Bima Wahyu Pratama (Universitas Hamzanwadi, 2025)
The development of digital technology in education has encouraged the birth of learning innovations that are more interactive, contextual, and meaningful. A professional teacher is required to have four competencies, namely pedagogical, professional, social, and personality. Of the four competencies, personality competencies occupy a central position because they are the foundation for building character, integrity, and role models for students. This research aims to 1) develop an experiential learning–storytelling-based e-module for social-emotional strengthening and 2) test the feasibility of an experiential learning–storytelling-based e-module for social-emotional strengthening. The research method used is the ADDIE (Analysis, Design, Development, Implementation, Evaluation) development model. The validation results showed that the e-module was appropriate (80%) and practical (83.5%). This e-module is effective in fostering social sensitivity, communication skills, self-reflection, as well as emotional and collaborative skills. Thus, it serves as a more meaningful and interactive learning innovation, while strengthening the balance between academic competence and the personality of prospective professional teachers. With this approach, prospective teachers are not only equipped with theoretical knowledge, but also reflective skills and empathy that are essential in building humanistic educational relationships. Storytelling as a learning method also encourages the creation of a learning atmosphere that is fun, communicative, and relevant to the context of students' lives.